Radiation Therapy for Gastrointestinal Cancers - Hong, Theodore; Das, Prajnan (Springer International Publishing : Imprint: Springer, 2017)
This up-to-date, hands-on manual offers clear guidance on contouring and treatment planning for both standard and advanced radiation therapy in patients with gastrointestinal cancers and simultaneously draws together the available relevant clinical data for each type of cancer with a view to driving treatment recommendations. The full range of malignancies is covered, including esophageal, gastric, pancreatic, hepatic, biliary, colon, rectal, and anal cancers and pelvic recurrences. Additional chapters are devoted to stereotactic body radiation therapy (SBRT) to the liver for metastatic disease. The management of gastrointestinal cancers with radiation therapy has become increasingly complex. Specifically, the emergence of new techniques such as SBRT and intensity-modulated radiation therapy (IMRT) has further increased the need to understand how to contour targets and organs at risk, how to perform safe treatment planning, and when to apply these technologies. In this context, Radiation Therapy for Gastrointestinal Cancers represents an ideal reference for both established clinical radiation oncologists and radiation oncology residents.
Keywords: Medicine.; Radiotherapy.; Gastroenterology.; Oncology.; elektronické knihy; electronic books